Protein analysis and characterization of recombinant clone Myt272-3 towards tuberculosis vaccine / Mohammed Maikudi Usman - Mohammed Maikudi , Usman (2017)
Tuberculosis (TB) infection is well-known for millennia and has been well apprehended since the end of 19th century. Robert Koch discovered its causative agent, Mycobacterium tuberculosis in 1882. TB vaccine has been in used for about a century, and antibiotics have been in place and utilized for more than six decades. They all work, yet 1.5 million deaths were recorded in 2014 due to TB which made it the leading infectious killer disease globally. Bacillus Calmette-Guérin (BCG), a live attenuated vaccine and is currently the most widely used. It has variability in effectiveness ranging from 0-80%, hence an urgent need for a better vaccine candidate is of paramount important. The recombinant clone (pET30a / Myt272-3 clone) constructed in Molecular Bacteriology and Toxicology Laboratory of University of Malaya was screened for its stability, and was found stable. The recombinant clone was transformed into BL21 (DE3) pLysS strain of Escherichia coli. The Myt272-3 protein was successfully expressed in pET30a / Myt272-3 clone. The molecular weight of the protein was found to be approximately 10.58 kDa as determined by SDS-PAGE and conformed to the MW computed by Expert Protein Analysis System (EXPASY MW bioinformatics tool). Protein BLAST (Basic Local Alignment Search tool) bioinformatics analysis indicated 81% homology with Phenolpthiocerol synthesis polyketide synthase I PpSA of Mycobacterium tuberculosis, MALDI-TOF analysis further validated the homology of the protein. The concentration of protein was determined by detergent-compatible method of protein assay. The protein was purified by both Nickel based (Nickel-nitrilotriacetic acid, Ni-NTA) and Cobalt based (Dynabeads®) affinity chromatographic techniques. Recently, computational biology approaches are found very useful for organizing and understanding huge data leading to the new field called immunoinformatics. Bioinformatics software were used to analyze the protein sequence for predictions of allergenicity, antigenicity, major histocompatibility complexes, I and II binding and B-cell epitope binding. Moreover, toxicity of epitopes was predicted via toxicity predictive tool. These predictive findings serve as a practical guide towards Mycobacterium tuberculosis peptide vaccine design and development.